Developmental Relations Among Behavioral Inhibition, Anxiety, and Attention Biases to Threat and Positive Information. Issue 1 (January 2017) - White, Lauren K.; Degnan, Kathryn A.; Henderson, Heather A.; Pérez‐Edgar, Koraly; Walker, Olga L.; Shechner, Tomer; Leibenluft, Ellen; Bar‐Haim, Yair; Pine, Daniel S.; Fox, Nathan A.
Abstract : This study examined relations between behavioral inhibition (BI) assessed in toddlerhood ( n  = 268) and attention biases (AB) to threat and positive faces and maternal‐reported anxiety assessed when children were 5‐ and 7‐year‐old. Results revealed that BI predicted anxiety at age 7 in children with AB toward threat, away from positive, or with no bias, at age 7; BI did not predict anxiety for children displaying AB away from threat or toward positive. Five‐year AB did not moderate the link between BI and 7‐year anxiety. No direct association between AB and BI or anxiety was detected; moreover, children did not show stable AB across development. These findings extend our understanding of the developmental links among BI, AB, and anxiety.